Market failures in market-based finance - Giovanni Di Iasio; Dominika Kryczka (European Central Bank (ECB), 2021)
We build a three-period model to investigate market failures in the market-based financial system. Institutional investors (IIs), such as insurance companies and pension funds, have liabilities offering guaranteed returns and operate under a risk-sensitive solvency constraint. They seek to allocate funds to asset managers (AMs) that provide diversification when investing in risky assets. At the interim date, AMs that run investment funds face investor redemptions and liquidate risky assets and/or deplete cash holdings, if available. Dealer banks can purchase risky assets, thus providing market liquidity. The latter ultimately determines equilibrium allocations. In the competitive equilibrium, AMs suffer from a pecuniary externality and hold inefficiently low amounts of cash. Asset fire sales increase the overall cost of meeting redemptions and depress risk-adjusted returns delivered by AMs to IIs, forcing the latter to de-risk. We show that a macroprudential approach to (i) the liquidity regulation of AMs and (ii) the solvency regulation of IIs can improve upon the competitive equilibrium allocations.
Keywords: D62; G01; G23; G38; 330; Market-based finance; regulation; investment funds; insurance companies and pension funds; market liquidity